Governance options of municipal actors for reurbanisation in medium-sized cities. An analysis by the example of Bamberg - Boeth, Henning (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
This paper examines the governance options for reurbanisation in medium-sized cities by using the example of Bamberg. The key questions are: Which planning approaches are developed in the areas of action housing and urban development to shape reurbanisation? How do local actor constellations and relationships shape the governance options? The contribution follows on debates about local reurbanisation drivers and an understanding of planning in terms of governance. The results show that Bamberg aimed to develop a conversion area and has thus implemented planning instruments and political-administrative structures. However, the use of the conversion areas by non-municipal actors in addition with municipal actors that are strongly guided by monetary considerations prevents the conversion in the further course and severely limits the governance options. As a result, a departure from the goal of a planned reurbanisation can be seen. The paper concludes by discussing the context under which growth policies for reurbanisation are developed and implemented.